Perlindungan Nasabah Muslim dalam Transaksi Non-Tunai Perspektif al-Dharuriyyat al-Khamsah: Protection of Muslim Costumers in Non-Cash Transactions a-Dharuriyyat al-Khamsah Perspective - Abadi, Said (Institut Agama Islam Sunan Giri Ponorogo, 2021)
This paper attempts to analyze customer protection practices in non-cash transactions in Indonesia and explore the perspective of al-dharuriyyat al-khams on the protection of Muslim customers in non-cash transactions. The trend of non-cash transactions in Indonesia has become increasingly widespread since 2014 when Bank Indonesia socialized the National Non-Cash Movement. However, along with these developments, there are several weaknesses and questions related to customer protection in general and Muslim customers in particular. Some security cases include loss of electronic money cards, failed transactions, sudden decrease in balance and the imposition of additional e-money fees, and several other cases. This type of research is literary research that uses a variety of library information (library research). While the approach used is a qualitative approach which refers to the data normatively. The results of the study conclude: first, the position of consumers/customers in non-cash transactions in Indonesia, even though the legal instruments are quite complete, are practically not sufficient to protect them properly. Second, based on the five principles of maintaining al-dharuriyyat al-khams, namely the protection of religion, soul, mind, lineage and property, it is clear that efforts to protect Muslim customers in non-cash transactions have been carried out but in a security system in transactions, customer data security systems, and socialization of important information related to customers still needs to be improved.